2017
DOI: 10.4317/jced.53722
|View full text |Cite
|
Sign up to set email alerts
|

Dentin bonding agent with improved bond strength to dentin through incorporation of sepiolite nanoparticles

Abstract: BackgroundThe study aims to investigate the effect of incorporation of sepiolite nanoparticles on the microtensile bond strength of an experimental dentin bonding to the human dentin.Material and MethodsThe sepiolite nanoparticles were incorporated into an experimental methacrylate-based dentin bonding system in concentrations of 0.0, 0.2, 1.0, 2.0, and 5.0 weight percents. The specimens were then ultrasonicated to finely disperse the nanoparticles in the adhesive matrix. The coronal enamel of 30 intact human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Kim et al also reported that the addition of Si nanofiller in the adhesive resulted in the highest µTBS values compared with the other groups [ 34 ]. Fallahzadeh et al reported similar findings and demonstrated that the addition of sepiolite (nanoparticles based on phyllosilicates) in the adhesive could improve its bond strength with dentin [ 35 ]. Our results are in conformity with these studies as we also observed that the addition of increasing concentrations of Si amplified the bond strength of the adhesives.…”
Section: Discussionmentioning
confidence: 88%
“…Kim et al also reported that the addition of Si nanofiller in the adhesive resulted in the highest µTBS values compared with the other groups [ 34 ]. Fallahzadeh et al reported similar findings and demonstrated that the addition of sepiolite (nanoparticles based on phyllosilicates) in the adhesive could improve its bond strength with dentin [ 35 ]. Our results are in conformity with these studies as we also observed that the addition of increasing concentrations of Si amplified the bond strength of the adhesives.…”
Section: Discussionmentioning
confidence: 88%
“…The results obtained in this study revealed no significant interference of the bioglass nanoparticles with the bond strength and mode of failure compared to the control DA. Previous studies also revealed that the incorporation of therapeutic nanoparticles, such as silver (0.1%), amorphous calcium phosphate (20%), or sepiolite (~2%), into two-step etch-and-rinse DA had no negative impact on shear bond and microtensile strength to dentin 43 , 44 . However, to precisely confirm MMP deactivation effects in terms of dentin-adhesive bonding ability, direct long-term microtensile experiments using DW, PBS or clinically relevant enzymatic environment are necessary, which will be further studied with in depth MMP deactivation mechanism study from released Cu ions.…”
Section: Discussionmentioning
confidence: 97%
“…The application of silane primer significantly influences the bonding of zirconia, with the adhesive layer proving to have low mechanical properties [ 203 ]. Incorporating GO sheets into silane primers is a viable option to improve the mechanical properties of the adhesive layer in resin composites bonded to ZrO 2 [ 204 ].…”
Section: Restorative Materialsmentioning
confidence: 99%